A humean reading of Nietzsche: problem of "Is vs. Ought" - Demirel, Ertürk. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
The aim of this study is to derive a Nietzschean solution to the inferential gap between the factual premises and the moral conclusion in a moral argument. I argue that the problem is not to be solved on the formal level. Formulating it as a tension between the metaphysically necessary relations between the facts the premises express and the freedom of will the conclusion expresses, I suggest that the solution to the problem must reconcile the freedom of action with necessity. I, then drawing from Hume in distinguishing between the factual necessity of causality, and psychological necessity of freedom of action as an inferential thread-guide, argue that causality of free will can be placed in the framework of the second sense of causality. In this sense, it is no more than a feeling a natural being enjoys, not a metaphysical principle applicable to moral actions. Yet the feeling itself cannot be discarded since as natural beings, human kind needs moral motivation and acts on the belief in causality of free will. That is to say, it is the psychological necessity of a natural being, rather than the metaphysical necessity of any kind, that opens up the infamous gap. Even if the gap between the factual premises and the moral conclusion cannot be closed on the formal inferential level, one can analyze what makes this gap possible as the key to the solution. If one focuses on the factual preconditions of the enjoyment of this feeling, one can have a guideline where one can infer moral conclusions from the factual premises, and the gap perhaps can be closed on the basis of this outline. I provide a reading of Nietzsche with this aim. The socio-political rules that historically trained an animal of free will, in this reading, may govern the proper use of “Ought” and indicate for the right place to look for an inferential guide applicable to the moral arguments. That is to say the solution of the problem lies in the conception of moral judgments as speech-acts. I conclude that the rules and the preconditions of the moral speech-acts can provide the key to the moral inferences.
Keywords: Ethics.